Comparing dropout predictors for two state-level panels using Grade 6 and Grade 8 data. Issue 6 (1st November 2016) - Franklin, Bobby J.; Trouard, Stephen B.
ABSTRACT: The purpose of this study was to examine the effectiveness of dropout predictors across time. Two state-level high school graduation panels were selected to begin with the seventh and ninth grades but end at the same time. The first panel (seventh grade) contained 29, 554 students and used sixth grade predictors. The second panel (ninth grade) included 31, 641 students and used eighth grade predictors. The predictors studied were age, poverty, attendance, gender, and standardized test scores. The data were analyzed using logistic regression. All variables were predictors of dropping out of high school. Age and poverty proved to be the most effective at discriminating between dropouts and graduates within each panel. Age became more effective with time. Attendance and test scores were stable indicators between panels. Gender predicted dropouts for only the ninth grade panel. Eighth graders that were female were approximately 22% less likely to drop out.